2020
DOI: 10.3390/nu12113223
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Plant-Origin Bio-Active Compounds, Intestinal Functionality, and Microbiome

Abstract: In recent years, plant-origin bio-active compounds in foods (staple crops, fruit, vegetables, and others) have been gaining interest, and processes to consider them for public health recommendations are being presented and discussed in the literature. However, at times, it may be challenging to demonstrate causality, and there often is not a single compound–single effect relationship. Furthermore, it was suggested that health benefits may be due to metabolites produced by the host or gut microbiome rather than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The intra-amniotic administration procedure was previously described by Tako et al [ 25 , 28 , 30 , 45 , 46 , 47 , 48 ]. On Day 17 of embryonic incubation, eggs with viable embryos were weighed and allocated into treatment groups ( n = 10) with equal weight distribution.…”
Section: Methodsmentioning
confidence: 99%
“…The intra-amniotic administration procedure was previously described by Tako et al [ 25 , 28 , 30 , 45 , 46 , 47 , 48 ]. On Day 17 of embryonic incubation, eggs with viable embryos were weighed and allocated into treatment groups ( n = 10) with equal weight distribution.…”
Section: Methodsmentioning
confidence: 99%
“…The intra-amniotic administration procedure was previously described by Tako et al [ 47 ]. On Day 17 of embryonic incubation, eggs with viable embryos were weighed and divided into seven groups ( n = 10) with approximately equal weight distribution.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that plant extracts may directly or indirectly act as a factor that elevates bioavailability of minerals from the diet. This most likely occurs due to fiber fermentation as well as bacterial production of short-chain fatty acids, and a subsequent decrease in pH may increase mineral solubility and subsequently their absorption (56). By contrast, phenolic acids and flavonoids have been shown to reduce the absorption of trace elements, such as iron, zinc, and copper, probably as a consequence of chelation by galloyl and catechol groups (57).…”
Section: Mineral Profilementioning
confidence: 99%